2018
DOI: 10.1039/c7cs00885f
|View full text |Cite
|
Sign up to set email alerts
|

Sensing and capture of toxic and hazardous gases and vapors by metal–organic frameworks

Abstract: Toxic and hazardous chemical species are ubiquitous, predominantly emitted by anthropogenic activities, and pose serious risks to human health and the environment. Thus, the sensing and subsequent capture of these chemicals, especially in the gas or vapor phase, are of extreme importance. To this end, metal-organic frameworks have attracted significant interest, as their high porosity and wide tunability make them ideal for both applications. These tailorable framework materials are particularly promising for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
285
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 608 publications
(286 citation statements)
references
References 184 publications
1
285
0
Order By: Relevance
“…Metal–organic frameworks (MOFs), also called porous coordination polymers (PCPs), are a class of porous materials commonly obtained by the facile hydrothermal or solvothermal reactions of metal ions and bridging organic ligands at relatively low temperatures . In the past two decades, extensive research has been devoted to developing new MOFs and to exploring their application potential in many fields, such as gas storage, separation, catalysis, sensing, and biomedicine . Early on, a handful of MOFs was found to show a low affinity toward water and a permanent porosity, and this class of hydrophobic MOFs later received increasing attention due to their potential for use in practical adsorption and separation processes, even under humid conditions or in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–organic frameworks (MOFs), also called porous coordination polymers (PCPs), are a class of porous materials commonly obtained by the facile hydrothermal or solvothermal reactions of metal ions and bridging organic ligands at relatively low temperatures . In the past two decades, extensive research has been devoted to developing new MOFs and to exploring their application potential in many fields, such as gas storage, separation, catalysis, sensing, and biomedicine . Early on, a handful of MOFs was found to show a low affinity toward water and a permanent porosity, and this class of hydrophobic MOFs later received increasing attention due to their potential for use in practical adsorption and separation processes, even under humid conditions or in water.…”
Section: Introductionmentioning
confidence: 99%
“…
as gas storage, [31][32][33][34][35] separation, [36][37][38][39][40][41][42][43][44][45][46][47][48] catalysis, [49][50][51][52] sensing, [53][54][55][56][57][58][59][60][61] and biomedicine. [62][63][64] Early on, a handful of MOFs was found to show a low affinity toward water and a permanent porosity, and this class of hydrophobic MOFs later received increasing attention due to their potential for use in practical adsorption and separation processes, even under humid conditions or in water.
…”
mentioning
confidence: 99%
“…Emerging as a new class of crystalline porous materials, metal-organic frameworks (MOFs) have attracted tremendous attention over the past decades in various fields, especially in gas sensing. [17] Many studies have indicated that their unique features of regular pores, open-metal sites, and tunable structures provided MOF materials with easy access for potentially overcoming the selectivity problem in gas sensor. [18][19][20][21][22] For instance, Tian et al reported that the ZnO@ZIF-8 nanorod sensor exhibited a better selectivity for formaldehyde compared with the pristine ZnO sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In general, as a specific analyte interacts with a luminescent MOFs, it may induce the change of luminescence intensity, either as an enhanced signal or depletion of the emission intensity ,. It is well known that interactions between the analyte and luminescent MOFs alter the MOFs electronic structure, and electron and energy transfer occur among the metal center, organic linker and analyte molecular.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In general, as a specific analyte interacts with a luminescent MOFs, it may induce the change of luminescence intensity, either as an enhanced signal or depletion of the emission intensity. [5,11] It is well known that interactions between the analyte and luminescent MOFs alter the MOFs electronic structure, and electron and energy transfer occur among the metal center, organic linker and analyte molecular. However, it is still a challenging issue to study the interaction between the analyte species and luminescent MOFs from molecular level, and to know exactly which active sites on a framework the analyte species prefer binding, resulting in the change of emission characteristics?…”
Section: Introductionmentioning
confidence: 99%